Improving sexual healthcare delivery for men in prison: A nurse‐led initiative. Issue 13 (1st April 2020) - Kelly, Carmel; Templeton, Michelle; Allen, Karen; Lohan, Maria
Abstract: Aims and objectives: The study aim was to develop and evaluate a nurse‐led sexual health service and health promotion intervention for men in prison. Background: Men in prison are particularly marginalised members of our society, negatively impacting on their ability to making healthy choices. In relation to sexual health, prison provides an opportunity for curative and preventive care, for an otherwise often hard‐to‐reach, priority population. Design: Practice development, audit and evaluation. Methods: Employing a practice development and participatory methodology, we empowered prison nursing staff to provide robust asymptomatic testing for sexually transmitted infections, including the management of chlamydia, with appropriate treatment and partner notification. Collaboratively with young men and nursing staff, a short animation video to promote the service was developed. A case note audit of 172 patients seen in the service during the 6‐month period 1 July 2018–31 December 2018 was undertaken. The Standards for Quality Improvement Reporting Excellence (SQUIRE, see Supplementary Material ) checklist was followed. Results: National outcome measures were exceeded for some clinical outcomes. During the 6‐month period, there were 12 chlamydia‐positive (7% positivity rate) and 3 gonorrhoea‐positive results. In addition, two new cases of syphilis were detected and a further two cases of known HIV were highlighted. There were seven cases of hepatitis C (3 previously diagnosed) and three cases of hepatitis B. A short animation Dick Loves Doot was developed. Conclusion: Successful partnerships between sexual health and prison healthcare services, in partnership with service users, can achieve well‐coordinated services and health promotion interventions. Relevance to clinical practice: This nurse‐led model of care increased detection and early treatment of asymptomatic STIs among men in prison, impacting positively the men, their partner (s) and the public health of the society to which they return.